2011
DOI: 10.1108/02683941111102155
|View full text |Cite
|
Sign up to set email alerts
|

Managerial trustworthiness and social exchange with the organization

Abstract: PurposeThe purpose of this paper is to examine how managerial trustworthiness and social exchange with the organization integrate with perceived organizational support to relate to supervisor‐rated job performance and self‐report organizational commitment.Design/methodology/approachA sample of 119 full‐time employees from a variety of occupations at a single organization completed surveys. Their supervisor rated job performance.FindingsThis paper finds that managerial trustworthiness was positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Specifically, consistent results emerged across three different countries for the spill-over effects from trust in the supervisor to trusting the CEO and the whole organisation (Costigan et al, 2004). Trust between subordinate and supervisor enhances perceptions of procedural (Holtz and Harold, 2008) and distributive justice (Brashear et al, 2005), and organisational support (Byrne et al, 2011). One of the most often articulated effects in the literature is the relationship between trust in the supervisor-subordinate relationship and organisational citizenship behaviour (OCB) (e.g.…”
Section: Organisational Levelmentioning
confidence: 99%
“…Specifically, consistent results emerged across three different countries for the spill-over effects from trust in the supervisor to trusting the CEO and the whole organisation (Costigan et al, 2004). Trust between subordinate and supervisor enhances perceptions of procedural (Holtz and Harold, 2008) and distributive justice (Brashear et al, 2005), and organisational support (Byrne et al, 2011). One of the most often articulated effects in the literature is the relationship between trust in the supervisor-subordinate relationship and organisational citizenship behaviour (OCB) (e.g.…”
Section: Organisational Levelmentioning
confidence: 99%
“…However, supervisors can engender perceptions of justice by providing resources fairly. Empirical studies have shown that managerial trustworthiness is positively related to job satisfaction, organizational commitment, and work attitudes (Byrne et al, ; Cho and Perry ). We expect that when employees perceive their manager as trustworthy, they extend these beliefs to the organization through transference and reciprocate in a way that is positive and beneficial to the organization.
Hypothesis 4a : Managerial trustworthiness is positively associated with employees’ job satisfaction. Hypothesis 4b : Managerial trustworthiness is negatively associated with employees’ turnover intention.
…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…When social exchanges transpire, a perceived commitment to counter in ways that are advantageous to the organization ensues. Trust, however, is required to commence the exchange (Bryne, Pitts, Chiaburu, & Stiner, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%